Proteomic Analysis Reveals the Positive Effect of Exogenous Spermidine in Tomato Seedlings’ Response to High-temperature Stress - Sang, Qinqin; Shan, Xi; An, Yahong; Shu, Sheng; Sun, Jin; Guo, Shirong (Frontiers in Plant Science, 2017)
ABSTRACT Polyamines are phytohormones that regulate plant growth and development as well as the response to environmental stresses. To evaluate their functions in high-temperature stress responses, the effects of exogenous spermidine (Spd) were determined in tomato leaves using two-dimensional electrophoresis and MALDI-TOF/TOF MS. A total of 67 differentially expressed proteins were identified in response to high-temperature stress and/or exogenous Spd, which were grouped into different categories according to biological processes. The four largest categories included proteins involved in photosynthesis (27 %), cell rescue and defense (24 %), protein synthesis, folding and degradation (22 %), and energy and metabolism (13%). Exogenous Spd up-regulated most identified proteins involved in photosynthesis, implying an enhancement in photosynthetic capacity. Meanwhile, physiological analysis showed that Spd could improve net photosynthetic rate and the biomass accumulation. Moreover, an increased high-temperature stress tolerance by exogenous Spd would contribute to the higher expressions of proteins involved in cell rescue and defense, and Spd regulated the antioxidant enzymes activities and related genes expression in tomato seedlings exposed to high temperature. Taken together, these findings provide a better understanding of the Spd-induced high-temperature resistance by proteomic approaches, providing valuable insight into improving the high-temperature stress tolerance in the global warming epoch.